The retina as a window into detecting subclinical cardiovascular disease in type 2 diabetes - Abbas S. Alatrany; Kishan Lakhani; Alice C. Cowley; Jian L. Yeo; Abhishek Dattani; Sarah L. Ayton; Aparna Deshpande; Matthew P.M. Graham-Brown; Melanie J. Davies; Kamlesh Khunti; Thomas Yates; Stephanie L. Sellers; et al. (Scientific Reports)
Abstract Individuals with Type 2 Diabetes (T2D) are at high risk of subclinical cardiovascular disease (CVD), potentially detectable through retinal alterations. In this single-centre, prospective cohort study, 255 asymptomatic adults with T2D and no prior history of CVD underwent echocardiography, non-contrast coronary computed tomography and cardiovascular magnetic resonance. Retinal photographs were evaluated for diabetic retinopathy grade and microvascular geometric characteristics using deep learning (DL) tools. Associations with cardiac imaging markers of subclinical CVD were explored. Of the participants (aged 64 ± 7 years, 62% males); 200 (78%) had no diabetic retinopathy and 55 (22%) had mild background retinopathy. Groups were well-matched for age, sex, ethnicity, CV risk factors, urine microalbuminuria, and serum natriuretic peptide and high-sensitivity troponin levels. Presence of retinopathy was associated with a greater burden of coronary atherosclerosis (coronary artery calcium score ≥ 100; OR 2.63; 95% CI 1.29–5.36; P = 0.008), more concentric left ventricular remodelling (OR 3.11; 95% CI 1.50–6.45; P = 0.002), and worse global longitudinal strain (OR 2.32; 95% CI 1.18–4.59; P = 0.015), independent of key co-variables. Early diabetic retinopathy is associated with a high burden of coronary atherosclerosis and markers of early heart failure. Routine diabetic eye screening may serve as an effective alternative to currently advocated screening tests for detecting subclinical CVD in T2D, presenting opportunities for earlier detection and intervention.